2021
DOI: 10.3390/brainsci11091192
|View full text |Cite
|
Sign up to set email alerts
|

ERP Indicators of Self-Pain and Other Pain Reductions due to Placebo Analgesia Responding: The Moderating Role of the Fight-Flight-Freeze System

Abstract: This study evaluates the modulation of phasic pain and empathy for pain induced by placebo analgesia during pain and empathy for pain tasks. Because pain can be conceptualized as a dangerous stimulus that generates avoidance, we evaluated how approach and avoidance personality traits modulate pain and empathy for pain responses. We induced placebo analgesia to test whether this also reduces self-pain and other pain. Amplitude measures of the N1, P2, and P3 ERPs components, elicited by electric stimulations, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 119 publications
(165 reference statements)
4
20
2
Order By: Relevance
“…Later these authors showed that informing in advance participants that they would receive electric shocks increased their pain-related fear that reduced the PA effect 22 . In line with these ndings, we have recently observed smaller reductions in pain ratings and smaller decreases in the P2 and P3 amplitudes of the ERP elicited by electric stimuli in higher fear-related trait scorers 23 .…”
Section: Personality Dispositional Factorssupporting
confidence: 86%
See 4 more Smart Citations
“…Later these authors showed that informing in advance participants that they would receive electric shocks increased their pain-related fear that reduced the PA effect 22 . In line with these ndings, we have recently observed smaller reductions in pain ratings and smaller decreases in the P2 and P3 amplitudes of the ERP elicited by electric stimuli in higher fear-related trait scorers 23 .…”
Section: Personality Dispositional Factorssupporting
confidence: 86%
“…These are new ndings, considering that the available research evidence does not yet allow more precise assignment of the different components to the various modulations of pain (see Ploner et al's review 69 ). Additionally, the present PA empathy ndings seem to be compatible with previous ndings showing that the observation of other's pain increased activation in the sensorimotor cortex, as expressed by increased central β(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)…”
supporting
confidence: 93%
See 3 more Smart Citations